Rethinking Committee Work in the Research Enterprise: The Case of Regenerative Gatekeeping - Jonathan C. Lewis; Aixa Alemán‐Díaz; Mona Behl; Sarah Kolesar; Lisa White; Brandon Jones; Corey Garza; Sharon Cooper (AGU Advances, 2022)
Abstract Committees touch nearly every facet in the science, technology, engineering, and mathematics research enterprise. However, the role of gatekeeping through committee work has received little attention in Earth and space sciences. We propose a novel concept called, “regenerative gatekeeping” to challenge institutional inertia, cultivate belonging, accessibility, justice, diversity, equity, and inclusion in committee work. Three examples, a hiring committee process, a seminar series innovation, and an awards committee, highlight the need to self‐assess policies and practices, ask critical questions and engage in generative conflict. Rethinking committee work can activate distributed mechanisms needed to promote change.